Pediatric Systemic Lupus Erythematosus: Learning From Longer Follow Up to Adulthood - Costagliola, Giorgio; Mosca, Marta; Migliorini, Paola; Consolini, Rita (Frontiers in Pediatrics, 2018)
Background: Pediatric systemic lupus erythematosus (pSLE) is a rare condition, representing approximately 10% of SLE cases. The aim of this study was to identify variables to improve the diagnostic awareness and management of pSLE patients. Methods: This retrospective study included 25 patients diagnosed with pSLE and followed at the University of Pisa. We collected data about clinical profile at disease onset and during a long-term follow-up, including disease activity, organ damage development, and treatments received. Results: The mean patient age at disease onset was 14.6 ± 1.6 years, and the mean follow-up period was 14.17 ± 8.04 years. The most common initial manifestations were arthritis, malar rash, and cytopenias. The median time to diagnosis since the first symptoms was 6 months, and was significantly longer in patients with hematological onset (54 months). During follow-up, the number of patients with renal involvement showed a significant increase, from 36% at diagnosis to 72.2% after 10 years of disease evolution. Patients who developed chronic organ damage maintained a higher time-averaged disease activity during follow-up and received a significantly higher dose of corticosteroids. Conclusion: Patients with immune cytopenia represent a group deserving strict clinical follow-up for the risk of evolution to SLE. Intense surveillance of renal function, early treatment and steroid-sparing strategies should be strongly considered in the management of pSLE patients.